Tattooed and/or Pierced Christians? : A Comparative Analysis of Catholic and Orthodox Perspectives on Body Modification - Mavropoulos, Angelos, (Eastern Church Identities ;, 2025)
Despite the widespread popularity of body modification, this study is the first to provide a comparative analysis of Catholic and Orthodox perspectives on tattoos and piercings. By examining historical, doctrinal, and ethical debates, the book explores scriptural interpretations, official Church teachings, and theological arguments. It also considers cultural and pastoral dimensions, shedding light on a controversial yet relevant issue in contemporary Christianity. As a comparative study, it not only deepens the understanding of Catholic and Orthodox traditions but also fosters interfaith and intercultural dialogue, promoting communication and mutual respect. By bridging historical perspectives with modern practice, this research offers valuable insights for theologians, scholars, and readers interested in an intersectional study of faith, identity, and personal expression.